Economic feasibility of producing olives for oil in the Sacramento Valley - Page, Collin (Kansas State University, 2023)
Extra virgin olive oil has become an important ingredient in the pantry of health-conscious consumers and foodies. This has increased the demand for olives that may be processed into extra virgin olive oil. There is, therefore, an opportunity to make investments in olive production to support this demand but it is important that it is assessed to be economically feasible. The purpose of this study is to determine the economic feasibility of high density olive orchard supplying processors of extra virgin olive oil in the Sacramento Valley. It also evaluated the sensitivity of this feasibility to oil prices, agronomic costs, and the debt-equity financing ratio. The analysis utilized a combination of primary and secondary data from private farming enterprises and extension reports. In order to ensure a substantial cash flow and to provide sufficient time for the establishment of the orchard, the analyses were conducted over a period of ten years. Once in full production in Year 5, the average net profit for the base scenario was estimated at $1,243 per acre. In addition to the base scenario, the feasibility analyses were conducted under seven alternative scenarios focusing on different levels of oil prices, irrigation cost, pest management costs, and harvest costs as well as acreage and debt-equity financing ratio. The results were summarized using a matrix that showed the economic feasibility as measured by net present values under the different scenarios. The results show that planting olives for extra virgin olive oil is economically feasible if the debt percentage to acreage ratio is kept below 0.15 to 0.20 percent when financing 40 percent or more of the operation. In the base scenario of the study, the net present value of the orchard was $150,648 at a discount rate of 5 percent and produced $404,066 of net profit once full production was achieved in the fifth year. This study shows that the planting of olives for the production of extra virgin olive oil in the Sacramento Valley is economically feasible under certain production and market conditions. Under these feasible conditions, the results show that it can produce a substantial level of income for the owners.
Keywords: Olive oil; Sacramento Valley; Economic feasibility; Extra virgin olive oil